2009
DOI: 10.1021/ma901647b
|View full text |Cite
|
Sign up to set email alerts
|

Microphase Separation in Sulfonated Block Copolymers Studied by Monte Carlo Simulations

Abstract: The underpinnings of microphase separation in symmetric poly(styrenesulfonate-block-methylbutylene) (PSS−PMB) copolymer melts were examined by Monte Carlo lattice simulations. The main challenge is understanding the effect of ion pairs in the PSS block on thermodynamics. We assume that experimentally determined Flory−Huggins interaction parameters are adequate for describing intermonomer interactions. Our model does not account for either electrostatic or dipolar interactions. This enables comparisons between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 30 publications
3
37
1
Order By: Relevance
“…(12), as we demonstrated in ref. [35]. At high temperatures we observe a single broad peak, characteristic of a disordered phase, but as the T * is lowered the multiple and narrow peaks develop which indicates the onset of the ODT.…”
Section: Simulation Results and Discussionmentioning
confidence: 74%
“…(12), as we demonstrated in ref. [35]. At high temperatures we observe a single broad peak, characteristic of a disordered phase, but as the T * is lowered the multiple and narrow peaks develop which indicates the onset of the ODT.…”
Section: Simulation Results and Discussionmentioning
confidence: 74%
“…One example would be poly(styrenesulfonate‐ block ‐polymethylbutylene) in which a random selection of the polystyrene monomers are sulfonated. Experimental studies as well as Monte Carlo simulations have shown that this system displays interesting phase behaviors . It would be interesting to explore the phase behavior of random copolymers with a non‐Markovian sequence distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies as well as Monte Carlo simulations have shown that this system displays interesting phase behaviors. [5][6][7] It would be interesting to explore the phase behavior of random copolymers with a non-Markovian sequence distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Computer simulations of such copolymers are more demanding because of the long-range interactions which have to be included. Some studies suggest that a minimal lattice model without longrange interactions can be used in the case of ion-containing block copolymers [16][17][18][19]. In this model the Flory interaction parameter, χ, between blocks is replaced by an effective interaction parameter that accounts for ionic interactions.…”
Section: Introductionmentioning
confidence: 99%